Associação Cristã de Moços no Brasil: um projeto de formação moral, intelectual e física (1890-1929) - Anderson da Cunha Baia (2012)
The present study addresses to the formation project of the Young Men's Christian Association (YMCA) in Brazil, since the institutional investment on physical, intellectual and moral-religious upbringing of their associates. The first headquarters of this Association wasfounded in England, at 1844, by the initiative of George Williams. Few years later, it was present in several regions of Europe and North of America. In Brazil, the city of Rio de Janeiro was the first one to host an YMCA, at 1893, created by the missionary North- American Myron August Clark. At the beginning of the 20th century, several attempts of creating new headquarters were observed in different parts of the country, however only three were consolidated: Rio de Janeiro (1893), Porto Alegre (1901) and São Paulo (1902). Despite of these three headquarters, the presence of Myron Clark at YMCA in Rio de Janeirocontributed for its characterization as being a box of resonance from which emanated knowledge and practices which would conduct the formation project of other headquarters. Based on the missionarys work in Brazil, as well as everything that was found out by him there, and from his experience at YMCA, in the United States of America, I have taken asmain purpose to understand the constitution of the formation project of the Young Men's Christian Association (YMCA), in Brazil, within a period between the beginning of the decade of 1890 and the end of the decade of 1920. The sources mobilized to enable this project were: magazines, newspapers and institutional documents pamphlets, letters, statutesand minutes of meetings , most of them had still not been discussed in previous studies regarding to History of Education and History of Physical Education. In this present study, I identified that the main point of the acmista project in Brazil was the moral-religious formation, focused on Christianity of the protestant doctrine. Even being an institution whichused to present the ecumenism at its speech, it was an Association with administrative structure, conducted specially by evangelical members. As a strategy of conversion, the institution supposes to be opened to receive individuals with any religious belief. If religion should constitute the principle of an acmista project, that was not necessarily the only one.The investments on the intellectual upbringing were intensified over the first two decades of the 20th century. The incentives offered by the YMCAs for alphabetization and preparations of the associates for acting on stores or even getting a secondary or superior course, beyondcontribute for these specific purposes, were constituted of strategies of incorporation of the associates to the acmista project which also included physical upbringing. To work the body through well oriented physical exercise was an indication of: health promotion; formation ofhygienic habits; moral formation; conformation of an efficient, strong and prepared body for working; and, also, intellectual development. Thus, gymnastics and sports, with different focus according to the current period, were required as practices which could materialize thepurposes of this kind of education. Intellect, body shape and moral/religion were central elements for the construction of the acmista project, which, whether it was initially planned on basis of knowledge and practices brought by Myron Clark when he had been in contact with the dynamic of the Brazilian culture even influenced by religious, politics, economics and educational factors , has been changed into another project, redesigned and adapted after disputes between several individuals involved on that.